Moving Space Gallery - Galerij Michel Dekeyser. - Moving Space, Gent; Galerij Michel Dekeyser, Pepingen (Gent : Moving Space Gallery, 1990)
Bracke, Jo ; Dejean, Michel ; Kane, Ian ; Lambrechts, Marc ; Marcase ; Roelstraete, Stefaan ; Thinot, Dominique ; 't Kindt, Jacques ; Visser Finholdt, Sonja ; Bourgeois, Paul ; Crab, Jan ; De Mey, Gaston ; Juchtmans, Jus ; Vandenbranden, Guy ; Vande Vyver, Ron ; Wagemans, Frank
artists represented by Moving Space Gallery, Gent & Galerij Michel Dekeyser, Pepingen, 1990
boek